Developing digital marketing relationship perspectives - Thaichon, Park; Ratten, Vanessa (emerald Publishing, 2021)
Developing Digital Marketing: Relationship Perspectivesprovides a holistic perspective about the role of digital marketing in the global economy, helping readers to understand the shift from traditional marketing to more novel and innovative forms